Decisions Parents Make When Faced With Potentially Life-Limiting Fetal Diagnoses and the Importance of Perinatal Palliative Care - Marc-Aurele, Krishelle L. (Frontiers in Pediatrics, 2020)
When parents face a potentially life-limiting fetal diagnosis in pregnancy, they then have a series of decisions to make. These include confirmatory testing, termination, and additional choices if they choose to continue the pregnancy. A perinatal palliative team provides a safe, compassionate, and caring space for parents to process their emotions and discuss their values. In a shared decision-making model, the team explores how a family’s faith, experiences, values, and perspectives shape the goals for care. For some families, terminating a pregnancy for any reason conflicts with their faith or values and pursuing life prolonging treatments in order to give their baby the best chances for survival is the most important. For others, having a postnatal confirmatory diagnosis of a life limiting or serious medical condition gives them the assurance they need to allow their child a natural death. Others want care to be comfort-focused in order to maximize the time they have to be together as a family. Through this journey, a perinatal palliative team can provide the support and encouragement for families to express their goals and wishes, as well as find meaning and hope.